Pengaruh Reward dan Motivasi terhadap Kinerja Karyawan di PT Bank Muamalat Indonesia Bandung - Akmal Tamami; Nur'aeni Nur'aeni (Masoem University, 2023)
Based on the observation results, the background of this research is the fluctuation in the number of customers and the number of employees. Which is suspected to be influenced by rewards and employee motivation at PT Bank Muamalat Indonesia Bandung Head Office. This study aims to determine how the influence of reward and motivation on employee performance either partially or simultaneously. The object of this study is the performance of employees at PT Bank Muamalat Indonesia Bandung Head Office. The type of research is quantitative associative with primary data types using data collection techniques in the form of observation, interviews, literature and questionnaires. While the sampling technique used a saturated sample where the entire population was sampled, namely all employees numbering 40 people. The results showed that there was a significant influence between rewards on employee performance of 77,8% with the results of the t test where the tcount > ttable value (11,552 > 2,024), there was a significant influence between motivation on performance employees by 78.7% with the results of the t test where the value of tcount > ttable (11,844 > 2,024), and simultaneously there is a significant influence between reward and motivation on employee performance is 83,6% with the results of the F test where the value of Fcount > Ftable (94,197 > 3,24).